Examination of the effectiveness of the educational initiatives from Salt Lake 2002 for implementation by Los Angeles 2028 - McKeel, Wesley Coleman (Πανεπιστήμιο Πελοποννήσου, 2022)
The International Olympic Committee’s (IOC) Olympic Agenda 2020 put in place a “roadmap for the IOC and the Olympic Movement” (International Olympic Committee, 2021). The three pillars of credibility, sustainability and youth were identified as the focal areas of the recommendations with plans of “safeguarding the Olympic values and strengthening the role of sport in society” (International Olympic Committee, 2021). Agenda 2020 “calls for a bunch of cost-reduction measures” (Manfred, 2014). It also emphasizes the importance of spreading Olympic values-based education (International Olympic Committee, 2021). With a focus on cost-savings and Olympic education, this thesis aims to measure the effectiveness of the educational initiatives from the previous two Olympic Games hosted in the United States (Atlanta 1996 and Salt Lake 2002), in order to provide a list of responsible recommendations for the Los Angeles 2028 organizing committee to implement in preparation for the upcoming Games. The initial examination into this topic revealed a few constraints, including the lapse in time since each of these Games actually took place, a lack of any sort of previous effectiveness study for the educational initiatives and an inability to unveil any sort of significant information about the educational programming of Atlanta 1996. These limitations narrowed the focus of this thesis and magnified the concentration provided to Salt Lake 2002. Through developed relationships with constituents of the Salt Lake Organizing Committee, information was gathered to conduct three different online, self-structured surveys with an emphasis on different educational initiatives (traditional education, health and infrastructure) and was delivered to a group of 138 total participants. Across all surveys, 31.9% of participants self-identified as males; 48.6% self-identified as females; 2.9% self-identified as non-binary/third gender; while, 16.7% declined to self-identify any gender. The majority of respondents fell into the 41-60 age range. 57.3% of the 138 participants were at least 41 years of age and no older than 60 years of age. Collected data was analysed in terms of mean and standard deviation values. Correlational analysis was employed to seek the relationships between the research variables concerning age, gender and education levels as indicated in the research questions. The results from these surveys reveal several data-supported findings. With the growing importance of Olympic education, emphasizing the values of Olympism, there is a great opportunity for Los Angeles 2028 to develop and measure the short-term and long-term effectiveness of educational initiatives. The Utah Olympic Park, a tangible legacy with a foundation to ensure future funding, proves to be the most effective educational initiative of Salt Lake 2002. While studying the Utah Olympic Park, the research provides evidence of a positive correlation between the age range of survey respondents and the overall effectiveness rating of the initiative. On the contrary, REACH: A Teacher’s Guide to the Olympic Winter Games and the Paralympic Games of 2002, the most effective traditional educational initiative, showcases an inverse relationship between age and effectiveness rating. Furthermore, the 2002 Education Website program provides a negative correlation between effectiveness rating and the educational level of participants. In an Olympic 4 world headlined by cheating, research shows a prioritization of the value of fair play, despite not being included by the IOC as one of the three Olympic values (friendship, excellence and respect) (International Olympic Committee, 2017-b). The study indicates females value respect more than friendship and excellence, highlighting an historical struggle for equality in sport. Lastly, all targeted initiatives of the 2002 Salt Lake Winter Olympic Games were successful in providing education around the values of Olympism.
Keywords: Olympic movement; Olympism; Olympic education; Olympic values; Ολυμπιακό κίνημα; Ολυμπισμός; Ολυμπιακή παιδεία; Ολυμπιακές αξίες; Olympic Games; Agenda 2020; Salt Lake 2002; Los Angeles 2028; Legacy; Traditional Education; Health Education; Infrastructure Education; Effectiveness; Analysis; Educational Initiatives